MONITORING THE LAND USE CHANGE IN CAMPUS 2 STKIP PGRI PONTIANAK - Ajun Purwanto; Galuh Bayuardi (Department of Urban and Regional Planning, Diponegoro University, 2016)
The aims of the research are: 1) investigating the changes of land-use occurring at campus 2 of STKIP PGRI Pontianak, 2) determining the tendency towards changes of land-use at campus 2 of STKIP PGRI Pontianak and, 3) mapping the land-use change at campus 2 of STKIP PGRI Pontianak from 2003 to 2011. The methods used in this research were survey and interpretation of the image of a multiple-color composite in 2003, 2008 and 2011 using GIS software. The data used were the types of land-use and the width of land-use change area. The data were analyzed by overlay method. The results have shown the following: 1) The changes of land use have been largely from forest land and paddy fields to settlement area; 2) The trend of the change is approaching to the North side, East side, South side and West side of the campus; 3) The characteristics of the extension of land-use changes from 2003 to 2011 are: settlement increased 66,110 m2, field service (restaurant) became 10,254 m2, the fields had added 17,097 m2, paddy field had decreased 25,211 m2, the forest area had decreased 104,327 m2 and educational facilities had increased 35,427 m2 while police station had extended 650 m2.